Consideraciones sobre la gobernabilidad como determinante del comportamiento electoral en Colombia: elecciones presidenciales de 2010 - Fredy A. Barrero; Carlos Meléndez (Colombia Internacional, 2011)
This article makes a contribution in the literature on electoral behavior in Colombia. Previous explanations have employed theories that emphasize the explanatory power of income, psico-social considerations and retrospective evaluation in order to assess the impact of programmatic, clientelistic and personalistic party-voter linkages on vote-choice. There is a gap in the literature that we propose to fill through the inclusion of governability appeals as a criterion that electors use when defining their electoral preferences. The fact that certain candidates are perceived with better conditions (or not) to overcome challenges to governability based on their links with powerful veto players is another factor that influences vote choice in addition to key variables (e.g. ideology). Original empirical information, based on the analysis of a national survey data, confirms the hypothesis proposed.